2018
DOI: 10.1007/s00709-018-1265-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a phospholipase (OsPLDα1) for drought tolerance in upland rice (Oryza sativa L.)

Abstract: This work aimed to evaluate the drought tolerance of transformed plants of the cultivar BRSMG Curinga that overexpress the rice phospholipase D α1 (OsPLDα1) gene. The productivity of independent transformation event plants of the OsPLDα1 gene was evaluated in an experiment where 19 days of water deficit were applied at the reproductive stage, a very strict growing condition for upland rice. The non-genetically modified cultivar (NGM) under drought treatment reduced productivity by 89% compared with that under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It has been shown that over-expression of chymotrypsin inhibitor-like 1 ( OsCPI1 ) in rice resulted in better survival and higher seed yield under severe drought (Huang et al ., 2007). The role of phospholipase in eliciting drought tolerance via modulating calcium-signalling pathway has also been demonstrated in rice (Abreu et al ., 2018; Deng et al ., 2019). These results suggest that hypomethylation in CHH context may govern regulation of candidate genes involved in desiccation stress response in Nagina 22.…”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that over-expression of chymotrypsin inhibitor-like 1 ( OsCPI1 ) in rice resulted in better survival and higher seed yield under severe drought (Huang et al ., 2007). The role of phospholipase in eliciting drought tolerance via modulating calcium-signalling pathway has also been demonstrated in rice (Abreu et al ., 2018; Deng et al ., 2019). These results suggest that hypomethylation in CHH context may govern regulation of candidate genes involved in desiccation stress response in Nagina 22.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, OsPLDα1 affects cold stress response through its product PA regulating the expression of OsDREB1 (Huo et al , 2016). Overexpression of PLDα1 in upland rice improved drought tolerance by maintaining the photosynthetic apparatus integrity (Abreu et al , 2018). Two chloroplast‐localized PLDs, OsPLDα4 and OsPLDα5, regulate herbivore‐induced direct and indirect defenses (Qi et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, PLD has been reported to be involved in several plant cellular processes, playing a significant role in seed germination, pollen tube development, and root hairs growth . Furthermore, PLD is directly involved in plant stress responses; for instance, AtPLDα1 regulates the abscisic acid (ABA) signaling, and overexpression of OsPLDα1 induces drought tolerance in rice . The suppression of PLDα1 in Arabidopsis enhances freezing tolerance, while suppression of PLDγ increases susceptibility to cold stress; these results indicate that each individual PLD gene could play a distinct role in response to plant stress.…”
Section: Introductionmentioning
confidence: 99%